Do participants in adjuvant breast cancer trials reflect the breast cancer patient population?. Issue 8 (May 2015) - Treweek, Shaun; Dryden, Ruth; McCowan, Colin; Harrow, Alison; Thompson, Alastair M.
Highlights Breast cancer trials are more inclusive than chronic disease trials. Despite this, it was rare for more than 45% of women to be eligible. Clinical and trial eligibility criteria are sometimes substantially different. Many women receive treatments tested in trials for which they would be ineligible.